Pengaruh Perubahan Tegangan Masukan Terhadap Efisiensi Energi Kompor Induksi - Budi Sudiarto; Justinus Dipo Nugroho; Faiz Husnayain; Agus R. Utomo; I Made Ardita (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2023)
Efficiency in energy use is essential for achieving national energy security. Dependence on energy supplies with high levels of imports can make a nation to be more susceptible to crises and dependence. It also includes the provision of energy sources for cooking needs. An electric induction cooker is one of the alternatives to the liquified petroleum gas (LPG) gas stove used for cooking. Given the high government import subsidy for LPG procurement, diversification of energy sources for cooking needs to be done. Cooking with an induction cooker is more efficient than cooking with a gas stove because it requires a shorter cooking time, and less heat energy is wasted. The energy efficiency of induction cookers ranges is approximately 80% or twice that of gas cookers ranges, which is at 40%. Nonetheless, the level of energy efficiency of induction cookers can be affected by the electricity supply voltage. Electricity conditions in Indonesia with a voltage service quality level of 220 V ± 10% result in the energy efficiency of induction cookers varying. This study analyzes the effect of input voltage variations on the energy efficiency of induction cookers. The input voltage was varied from 230 V to 200 V with a difference of 10 V using four brands of induction cookers. The test results indicate that the efficiency is directly proportional to the input voltage, where the higher the input voltage will provide the greater the induction cooker’s energy efficiency.